Portrait of sexual violence in oil palm plantation - Gustia Saputri, Suci (BKM Public Health and Community Medicine, 2021)
Objective: This paper aims to examine sexual violence against female workers in oil palm plantations. Content: Sexual violence is all unwanted sexual behavior, both physical and psychological, which usually occurs in women. Sexual violence can occur because The strong patriarchal culture in Indonesia makes the perpetrators think that they are stronger and have high positions so that they can do anything to their subordinates, especially those who work in a female minority. In addition, a quiet place is also one of the causes of violence, such as plantations. Plantation areas are far from settlements and minimal lighting makes the perpetrators free to carry out their actions. Most of the victims are helpless because of economic pressure. Offenders in high positions seem to have full control over the economy and make victims surrender to the pressures and conditions they face, often even being threatened with losing their jobs. The perpetrators think that sexual issues are commonplace with workers who are or have been married. On the other hand, they seem to be seen as having no value other than body and sexuality. The workers' lack of knowledge about violence makes them unaware of being victims of violence even though verbally. This matter cause many losses such as career disruption, experiencing anxiety and depression.The still low reporting is because the victim does not know where to complain, if he reports to the superior he is afraid of not being responded to and there is no continuation, because the perpetrator is one of his superiors, and there is no legal protection for the victim. What is very unfortunate is that there are many “stealth workers'' because they are not registered at the Manpower Office. This should be a concern with cross-sector cooperation as an effort to improve worker welfare and safety.